INVENTARISASI SERANGGA POLINATOR DI LAHAN PERTANIAN KACANG PANJANG (Vygnacylindrica) KOTA PEKANBARU DAN PENGEMBANGANNYA UNTUK SUMBER BELAJAR PADA KONSEP POLA INTERAKSI MAKHLUK HIDUP DI SMP - Meri Handani; Mariani Natalina; Elya Febrita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The research was conducted to investigate diversity insectpollinatorsinlong beans (Vygna cylindrica) agricultural land Pekanbaru City in February to June,2014. Research results are used to development of instructional media in the form oflearning modules, student worksheet and interactivemediaofthe results ofthe inventoryofinsectpollinators.This research was carried out by two stage that is the field researchstage and media development stage. The research was conducted at 3 locationsobservation using total sampling at each station. Station I: located in the Tenayan RayaDistrict, Seroja Kulim Street. Spacious long beans gardenrange between ± 60x 40meters. Station II: located in the Rumbai District, Palas Village, Tengku Ibrahim StreetSpacious long beans garden ±60x 40meters.Station III : located in the Tampan District,Bina Widya Street, faculty of Agriculture, University of Riau. Spacious longbeansgardenrange between±25x 30 meters the inventory of insect pollinators andenvironmental physical parameters include temperature, humidity and light intensity.The results showed that there are seven species of insect pollinator sare found in thelong beans (Vygna cylindrica) agricultural land Pekanbaru City. Belonging to 6 familiesand 3 orders that the Order Hymenoptera Family Anthporidae (1 species), FamilyApidae (2 species), Family Pesvinae (1 species). Order Diptera Family Syripidae (1species) and Order Lepidoptera Family Lycanidae (1 species). temperatures rangedbetween from 25.4 to 31.9 OC, humidity ranged between 69-84% and light intensityranges from 1673.2 to 3173.5 all physical environmental factors are still within therange of tolerance. Results of the study can be used as a source of learning namelylearning modules, student worksheets and interactive media on the concept ofinteraction patterns of living creatures in Junior High School.Key Word: Type Insect Pollinator, Bean, Learning Resources.